Integrating Artificial Intelligence in EFL Classrooms: Opportunities and Challenges for Indonesian Teachers - Mulkiyah, Ummu (Journal Corner of Education, Linguistics, and Literature, 2024)
This study examines how English as a Foreign Language (EFL) teachers in public senior high schools in Ogan Komering Ulu Timur (East OKU), South Sumatera, Indonesia, perceive and use artificial intelligence (AI) tools in their classrooms. Using a qualitative descriptive design, data were collected through semi-structured interviews, classroom observations, and document analysis with six EFL teachers. The findings reveal that the teachers generally have positive attitudes toward AI, particularly because of its ability to provide immediate feedback, encourage learner autonomy, and increase student motivation. However, practical implementation is challenged by limited infrastructure, including unstable internet connectivity and inadequate school facilities, as well as gaps in pedagogical competence and concerns over ethical misuse by students. A strong need for localized, curriculum-linked professional development programs tailored to AI tools was also expressed by teachers. The study found that integrating AI effectively in Indonesian EFL contexts requires more than just easy access to technology. It also needs well-designed training, investment from schools and universities, and guidelines to ensure ethical use of AI. The research proffers pragmatic insights for teachers, policymakers, and curriculum designers seeking to ameliorate the discrepancy between AI's potential and its actuality in language education.